2023
DOI: 10.3389/fpls.2022.1027279
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability studies of grain Fe and Zn contents of pearl millet (Pennisetum glaucum L.) in West Africa

Abstract: Micronutrient malnutrition is a major challenge in Africa, where half a million children die each year because of lack of micronutrients in their food. Pearl millet is an important food and fodder crop for the people living in the Semi-Arid regions of West Africa. The present study was conducted to determine the stability, combining ability, and gene action conditions of the high level of Fe and Zn content in grain and selected agronomic traits. Hence, eight genotypes were selected based on the availability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The analysis also showed that the days to 50% flowering, earhead girth, grain yield/plot, fodder yield/plot, 1000 grain weight, iron content, and zinc content had larger mean sum of squares for SCA, which suggested a preponderance of non-additive gene action to influence these features. Therefore, heterosis breeding will be fruitful (Dhuppe et [6,9,25,7] .…”
Section: Resultsmentioning
confidence: 99%
“…The analysis also showed that the days to 50% flowering, earhead girth, grain yield/plot, fodder yield/plot, 1000 grain weight, iron content, and zinc content had larger mean sum of squares for SCA, which suggested a preponderance of non-additive gene action to influence these features. Therefore, heterosis breeding will be fruitful (Dhuppe et [6,9,25,7] .…”
Section: Resultsmentioning
confidence: 99%